2020
DOI: 10.31926/but.fwiafe.2020.13.62.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training Parameters on the Ability of Artificial Neural Networks to Learn: A Simulation on Accelerometer Data for Task Recognition in Motor-Manual Felling and Processing

Abstract: Producing dynamic, real-time reliable data on the performance of timber harvesting operations has gained lately a lot of momentum due to the necessity to proactively manage the fleets of machines and machine allocation and to better monitor them in different operational environments to be able to understand their capability and performance. Techniques of Artificial Intelligence (AI) have been used recently to get accurate data at a low cost in many fields of science. In particular, the use of Artificial Neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Fitness and sleep bands have been used (1) to monitor the physical activity and sleep patterns of forestry workers in order to understand how these factors may contribute to workplace hazards [89], and (2) to predict forestry worker fatigue by comparing heart rate and step count data to reaction and decision-making times [90]. Smartwatches paired with heart rate monitor chest straps have been used to evaluate workload associated with manual tree felling [91], while external accelerometers attached to machines have been used to develop ANNs that classify the activities of manually-driven bandsaws [92] and recognize activities associated with manual felling [93]. Preliminary activity recognition models have been developed for cable yarding work phases using a combination of smartphone sensor (global positioning system (GPS) and inertial measurement unit (IMU)) and camera data [66].…”
Section: Plos Onementioning
confidence: 99%
“…Fitness and sleep bands have been used (1) to monitor the physical activity and sleep patterns of forestry workers in order to understand how these factors may contribute to workplace hazards [89], and (2) to predict forestry worker fatigue by comparing heart rate and step count data to reaction and decision-making times [90]. Smartwatches paired with heart rate monitor chest straps have been used to evaluate workload associated with manual tree felling [91], while external accelerometers attached to machines have been used to develop ANNs that classify the activities of manually-driven bandsaws [92] and recognize activities associated with manual felling [93]. Preliminary activity recognition models have been developed for cable yarding work phases using a combination of smartphone sensor (global positioning system (GPS) and inertial measurement unit (IMU)) and camera data [66].…”
Section: Plos Onementioning
confidence: 99%
“…Most of the resource and process monitoring activities could benefit to a large extent from using the latest technologies of the artificial intelligence and machine learning to support real-time decision making and to set the ground for improvements. While no studies were identified to evaluate the industry’s needs for such technologies in Romania, some small-scale tests have already proven their usefulness, in terms of cost saving and safety [ 8 , 9 , 10 ]. In addition, the operational level has been identified in international forestry to be one of the potential beneficiaries of sensor-based and machine learning implementations [ 8 , 9 , 10 , 11 , 12 ], which enabled significant resource savings and safety improvements.…”
Section: Introductionmentioning
confidence: 99%
“…While no studies were identified to evaluate the industry’s needs for such technologies in Romania, some small-scale tests have already proven their usefulness, in terms of cost saving and safety [ 8 , 9 , 10 ]. In addition, the operational level has been identified in international forestry to be one of the potential beneficiaries of sensor-based and machine learning implementations [ 8 , 9 , 10 , 11 , 12 ], which enabled significant resource savings and safety improvements. At this level, manual-dominated tasks have been approached in forestry under the umbrella of the so-called human activity recognition, which has been implemented by the use of various data collection platforms and machine learning techniques e.g., [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations